Newspaper coverage of Colorado's 2016 End of Life Options Act. (September 2020) - Lauffer, Kimberly A.; Baker, Sean; Seely, Natalee K.
Since 2014, several states have introduced and passed legislation permitting aid in dying. In Colorado, Proposition 106, the End of Life Options Act, passed November 8, 2016, with 65% of Coloradans approving the law. The kind and tone of content newspapers include and omit regarding contentious issues like end-of-life legislation is important because these representations reflect and influence public opinion. This study found a relationship between item type and overall stance, as well as a difference in the content produced by journalists and laypersons or columnists.